ANTIGENIC PROPERTIES OF ARTIFICIAL POLYEPITOPE HIV IMMUNOGEN - A. P. Rudometov; N. B. Andreeva; A. N. Chikaev; N. S. Shcherbakova; O. N. Kaplina; L. I. Karpenko (Сибирский научный медицинский журнал)
The development of immunogen being capable of providing protection against HIV-1 infection and progression is still topical and unsolved challenge. Since HIV-1 demonstrates strong genetic variability, an efficient vaccine should provide protection against a number of various virus strains. Design of immunogen with capacity to induce broadly neutralizing antibodies to HIV is believed to solve this issue. As distinct from usual antibodies, bNAbs interact with conservative epitopes providing protective immunity to overwhelming majority of HIV strains. Our study aims to construct and analyze antigenic features of polyepitope HIV-immunogen nTBI comprising epitopes recognized by bNAbs. Materials and methods. We used previously designed TBI protein as molecule-carrier and obtained on this basis protein’s modified variant nTBI. It includes epitopes recognized by bNAbs 10E8, 4E10, 2F5, as well as linear mimetic of conformation epitope bNAb VRC01. Immunoblotting was used to analyze antigenic properties of epitopes in composition of nTBI. To purify nTBI, we used metal chelate chromatography. To study immunogenic properties, we immunized rabbits with purified nTBI preparation. Specific activity of sera from immunized rabbits was identified using ELISA. Affine chromatography on protein A was used to obtain IgG from sera of rabbits. Virus-neutralizing activity of purified IgG was detected in neutralization test using recombinant virus HIV-1 92BR025. Results. Immunogen nTBI comprising epitopes recognized by bNAbs was constructed. We obtained protein nTBI producer providing production of target protein up to 30 % of the amount of producer cell proteins. We showed that in the context of nTBI protein linear epitopes retain their antigenic properties. When immunizing rabbits, we found nTBI inducing production of antibodies capable of neutralizing recombinant HIV-1 strain 92BR025. Conclusion. We demonstrated principal possibility of the use of artificial TBI protein as a scaffold molecule to expose epitopes recognized by broadly neutralizing antibodies.